2018
DOI: 10.1007/s11908-018-0609-x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Trends and Treatment Options in Gram-Negative Ventilator-Associated Pneumonia

Abstract: Rapid identification technologies and phenotypic methods, new therapeutic strategies, and novel treatment paradigms have evolved in an attempt to improve treatment outcomes for VAP; however, clinical data supporting alternative treatment strategies and adjunctive therapies remain sparse. Importantly, new classes of antimicrobials, novel virulence factor inhibitors, and beta-lactam/beta-lactamase inhibitor combinations are currently in development. Conscientious stewardship of new and emerging therapeutic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 126 publications
5
24
0
3
Order By: Relevance
“…VAP is commonly caused by Pseudomonas aeruginosa , Klebsiella pneumonia , and Acinetobacter baumannii globally. It is important that the antimicrobial therapy be right in the first time in VAP patients, because the pathogens associated with inappropriate initial therapy are usually antibiotic-resistant strains of these pathogens, so patients at high risk of infection with these organisms initially needed to receive a combination of agents providing a very broad spectrum of coverage (Weiner et al, 2016; Rhodes et al, 2018). This review aims to summarize the available knowledge on drug prevention and control of VAP, taking profit from the recommendations of several health organization such as the American Thoracic Society with the Infectious Disease Society of America (Kalil et al, 2016), the Centers for Disease Control and Prevention (CDC) (Tablan et al, 2004), the European Task Force on VAP (Torres and Carlet, 2001), the Society for Healthcare Epidemiology of America, and the Institute for Healthcare Improvement (Klompas et al, 2014), as well as the recently major guidelines for the management of VAP (Kalil et al, 2016; Timsit et al, 2017a; Torres et al, 2017), and we hope that our clinicians know more about the initial therapies and treatment strategies of VAP, and we can investigate and focus on the management of the disease in future.…”
Section: Introductionmentioning
confidence: 99%
“…VAP is commonly caused by Pseudomonas aeruginosa , Klebsiella pneumonia , and Acinetobacter baumannii globally. It is important that the antimicrobial therapy be right in the first time in VAP patients, because the pathogens associated with inappropriate initial therapy are usually antibiotic-resistant strains of these pathogens, so patients at high risk of infection with these organisms initially needed to receive a combination of agents providing a very broad spectrum of coverage (Weiner et al, 2016; Rhodes et al, 2018). This review aims to summarize the available knowledge on drug prevention and control of VAP, taking profit from the recommendations of several health organization such as the American Thoracic Society with the Infectious Disease Society of America (Kalil et al, 2016), the Centers for Disease Control and Prevention (CDC) (Tablan et al, 2004), the European Task Force on VAP (Torres and Carlet, 2001), the Society for Healthcare Epidemiology of America, and the Institute for Healthcare Improvement (Klompas et al, 2014), as well as the recently major guidelines for the management of VAP (Kalil et al, 2016; Timsit et al, 2017a; Torres et al, 2017), and we hope that our clinicians know more about the initial therapies and treatment strategies of VAP, and we can investigate and focus on the management of the disease in future.…”
Section: Introductionmentioning
confidence: 99%
“…It works well against MDR Pseudomonas aeruginosa and ESBL Klebsiella pneumoniae and has excellent lung and urinary penetration. A systematic review found that 90% of MDR strains of P. aeruginosa were susceptible, and a study of 5057 ESBL producing isolates of E. coli and K. pneumoniae found that 91.3% were susceptible [30,34,35]. With high levels of clinical efficacy and low levels of resistance, it is seemingly ideal for GNB infections.…”
Section: Fosfomycinmentioning
confidence: 99%
“…A. baumannii has the propensity for biofilm formation, making it particularly difficult to eradicate in certain conditions (notably on blood and urinary catheters and endotracheal tubes) [23]. According to the National Healthcare Safety Network (NHSN), A. baumannii is the fifth most common VAP pathogen, accounting for 6.1% to 7.5% of all cases [24,25]. Despite only 2% of HAIs are caused by Acinetobacter spp., crude mortality in patients with A. baumannii infections can be as high as 75% [3,26].…”
Section: Epidemology Of Mdr and Xdr A Baumannii Infectionsmentioning
confidence: 99%